Policy level engagement for Investment on scaling CSAPs at least one sub-national level government - Jat, Mangi Lal; Agarwal, Tripti (2017)
There has been growing concern for policy level initiatives and investment priorities required for scaling climate smart agriculture practices (CSAPs). Over a period of 5 years (2013-2017), science based evidence has been generated on key scalable climate smart agriculture under the CCAFS flagship project on CSA in collaboration with CRPs on Wheat, Maize, Rice agrifood systems as well as range of partnerships (NARS, NGOs, Private Sector, Farmer organizations etc). CIMMYT-CCAFS in collaboration with number of sub-national, national and international stakeholders informed the key policy planners, Governments and development agencies on these CSAPs through several consultations, communication materials (policy brief, video, research articles etc), organizing several events (field days, travelling seminars, workshops, policy dialogues, training programs etc) and generated awareness among the different stakeholders. These systematic efforts have led to up scaling of CSAPs through their mainstreaming in investment programs to address the issue of natural resource degradation, environmental pollution and climatic risks. This document provides evidence base on policy level engagement process, partnerships and events for outscaling CSAPs by the sub-national governments and other key stakeholders.